Microneedling Radiofrequency for Acne Vulgaris and Post-Acne Scarring: A Case Report - Vesri Yossy; Satya Wydya Yenny; Lilik Norawati (HM Publisher, 2022)
Background. There are various therapeutic modalities for acne and post acne scarring, but the best option is to have a safe, effective with affordable cost such as monotherapy or combination therapy. One of the recommended combination therapy for acne vulgaris with atrophic acne scars is microneedling radiofrequency which can improve skin structure. Case presentation. A 25 years old male with moderate comedonal acne vulgaris and severe scarring. The patient came with complaints of uneven skin surface on both cheeks, forehead and chin which had been felt to increase since 3 years ago. The appearance of acne on the face has been felt since 12 years ago. The patient's parents and sister also had acne complaints. On dermatological examination, on the forehead, temples, cheeks, nose and chin found blackheads, whiteheads, papules, hyperpigmented macules, multiple atrophic acne scars. The treatment choice for this patient is microneedling radiofrequency in combination with topical therapy. Discussion. The combination of microneedling with radiofrequency is one of the therapeutic modalities for acne vulgaris and also post-acne scarring with minimal side effects. In the evaluation for 2 weeks after the procedure, this patient did not complaint of any adverse events.